Bill colour pattern in Bewick's swan: information on sex and body size displayed on face?. Issue 1 (2nd January 2018) - Ciach, Michał; Czyż, Stanisław; Wieloch, Maria
Abstract : Ornamental traits in birds (plumage/bare part colours) have been shown to provide information on diverse aspects of individual quality and behaviour. In bird species with achromatic plumages (uniformly white, grey or black), signals encoded in bare parts are the major mode of visual communication. In this study we analysed the influence of sex, age, body condition and selected biometric traits on the bill colour pattern in Bewick's swans Cygnus columbianus bewickii . The results indicate that sex and body size (weight and tarsus length) are associated with the bill colour pattern in Bewick's swans. Individuals with a larger black area on the bill were heavier and had a longer tarsus. Moreover, females had more black on their bills than males did. Age, head length and body condition index were not significantly related to bill colour pattern. The present work indicates that Bewick's swans may display information on their sex and size by means of their bill colour pattern. These findings also suggest the possibility that swans can remotely quantify one another's traits from the appearance of their bill colouration. Proper assessment of an opponent or of mate quality during face-to-face signalling may help birds to avoid unnecessary interaction or to maintain bonds between mates and family groups.